Environmental Care Character Education in Animated Film Dr. Seuss The Lorax - Evi Fitriana; Kukuh Wurdianto (Budapest International Research and Critics University, 2022)
The aims of this research is to examine the animated film Dr.Seus The Lorax. The storyline in this film is relevant to the goal of character education, especially caring for the environment. This study will analyze the moral content and character of caring for the environment in the Dr. Seuss The Lorax film. The research method used is a qualitative content analysis. The data source in this study is an animated film with the title Dr. Seuss The Lorax, directed by Chris Renaud Kyle Balda. Data collecting in this study using documentation techniques. This film is the right medium to share and create self-awareness for the community about the environment. Dr. Seuss' The Lorax invites the audience to take action to save the environment and motivates the audience to treat nature as God's creation.